2021
DOI: 10.34172/ps.2021.44
|View full text |Cite
|
Sign up to set email alerts
|

Coumestrol alleviates oxidative stress, apoptosis and cognitive impairments through hippocampal estrogen receptor-beta in male mouse model of chronic restraint stress

Abstract: Background: Coumestrol is well-known as a natural estrogen receptor-beta modulator. Since the role of estrogen receptors in controlling stressful situations has already been reported and their cognitive functions in hippocampus seem to be independent of sexual tasks, the aim of this study was to investigate the improving effects of this phytoestrogen on negative consequences of exposing male mice to chronic restraint stress. Methods: This study was divided into two separate but consecutive phases. In the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…These findings indicate that the metabolic action of coumestrol is ERβ-dependent. In addition, Fekri et al [ 32 ] recently reported that the memory enhancing and anxiolytic effects of coumestrol were reversed by treatment with an ERβ-selective antagonist in a male mouse model of chronic restraint stress. In their study, the antioxidant and anti-apoptotic effects of coumestrol in brain tissue were lost following co-administration with an ERβ antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that the metabolic action of coumestrol is ERβ-dependent. In addition, Fekri et al [ 32 ] recently reported that the memory enhancing and anxiolytic effects of coumestrol were reversed by treatment with an ERβ-selective antagonist in a male mouse model of chronic restraint stress. In their study, the antioxidant and anti-apoptotic effects of coumestrol in brain tissue were lost following co-administration with an ERβ antagonist.…”
Section: Discussionmentioning
confidence: 99%